Theoretical and experimental research on the mechanical properties of magnetorheological elastomers based on PDMS - Huang, Xuewei; Li, Li; Ruan, Xiaohui (Frontiers in Materials, 2023)
Magnetorheological Elastomers (MREs) are smart materials with the ability to modulate their mechanical properties by changing the external magnetic fields, offering extensive potential for applications requiring variable stiffness and damping devices. A comprehensive mechanical model that explains the influence of loading conditions on the performance of MRE is crucial for understanding their intrinsic mechanisms during operation, and for the design, analysis, and improvement of intelligent energy dissipation and vibration control devices based on MRE. In this study, a four-parameter mechanical model was established to reveal the intrinsic mechanisms about the effects of external magnetic fields, loading frequency, and strain amplitude on the storage modulus, loss modulus, equivalent stiffness, and equivalent damping of MRE materials. The dynamic mechanical properties of the MRE materials prepared from carbonyl iron powder and PDMS were tested, and parameter identification of the established model was performed. The comparison results between the theoretical model analysis and the testing results demonstrated that the proposed mechanical model effectively characterizes and predicts the mechanical behavior of MRE materials. Furthermore, based on the prepared MRE materials, a stiffness-controllable energy dissipator operating in shear mode was designed and fabricated, and the mechanical performance of the shear energy dissipator was experimentally evaluated. This research provides a basis and guidance for the design and mechanical performance analysis of devices based on MRE, confirming the feasibility of MRE materials as core components in intelligent energy dissipation devices.